Transcriptome Profiling of the Ovarian Cells at the Single-Cell Resolution in Adult Asian Seabass - Liu, Xiaoli; Li, Wei; Yang, Yanping; Chen, Kaili; Li, Yulin; Zhu, Xinping; Ye, Hua; Xu, Hongyan (Frontiers in Cell and Developmental Biology, 2021)
Single-cell RNA sequencing (scRNA-seq) are widely adopted for identifying the signature molecular markers or regulators in cells, this would benefit defining or isolating various types of cells. Likewise, the signature transcriptome profile analysis at single cell level would well illustrate the key regulators or networks involved in gametogenesis and gonad development in animals, however, there are limited scRNA-seq analysis on gonadal cells in lower, especially in the sexual reversal fish species. In this study, we analyzed the molecular signature of several distinct cell populations of Asian seabass adult ovaries through scRNA-seq. We identified five cell types, also successfully validated some specific genes of germ cells and granulosa cells. Likewise, we found some key pathways involved in ovarian development that may concert germline-somatic interactions. Moreover, we compared the transcriptomic profiles across fruit fly, mammals and fish, thus uncovered the conservation and divergence in molecular mechanisms that might drive ovarian development. Our results provide basis for studying the crucial features of germ cells and somatic cells, which will benefit the understandings of the molecular mechanisms behind gametogenesis and gonad development in fish.